Vorhersagbarkeit konvektiver Niederschläge: Hochauflösende Ensemblesimulationen für Westafrika - Maurer, Vera (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2014)
During the West African Monsoon, convective systems generate the largest part of annual precipitation. We investigate their predictability by conducting high-resolution ensemble simulations with the COSMO model, focusing on the impact of the land surface. Are land-surface – atmosphere interactions in West Africa as important for precipitation forecasts as larger-scale conditions? What are the main physical processes?